(untitled) (Journal of Oriental Studies, 2024)
David Hovhannisyan has his own school of Oriental Studies in Armenia, a school unifying his students working in the field, and, of course, he has his own style and path in Oriental Studies. I have noticed that his students are clearly influenced by Professor Hovhannisyan’s research and pedagogical style, which is evident both in their presentations and publications. this is a proof of the school’s success and potential of continuation.